La gestión de información estadística relacionada con las actividades formativas en la Universidad Virtual de Salud. - Cordoví Hernández, Valia Dalgis; Pardo Gómez, C. María Elena; Rodríguez Beltrán, C. Nancy María; López Hung, Eduardo (MEDISAN)
Introduction: Information and communications technologies have originated unforeseeable and vertiginous changes in the different spheres of life. Objective: To characterize the current state of the statistical information management related to the training activities in the Health Virtual University in Santiago de Cuba. Methods: A descriptive and longitudinal study of evaluation during the school course 2016-2017 was carried out in the Medical Sciences University in Santiago de Cuba. Results: The managers had few years of experience as activists of UNIVERS; they took advantage from varied primary information sources to gather the information; there was no uniformity in the models of primary records and the use of computer tools was limited which contributed to organize, to process, to file, to control, to recover and to make faster the statistical information. Likewise, edition and emission of manual certificates was a doubtful and difficult process. Conclusions: It was determined that UNIVERS managers not always perceived the potentialities of technologies for obtaining statistical information and that, although there were literacy activities carried out using the tools offered by this training platform, there was scarce use of them to guarantee an appropriate analysis, control and emission of the statistical information of training activities and the teaching open resources emerging in the Health Virtual University.